Novi pristopi k zdravljenju akutne limfoblastne levkemije pri otrocih - Karas Kuželički, Nataša (Farmacevtski vestnik, 2014)
Acute lymphoblastic leukemia (ALL) is the most common cancer in 1 to 10 years old children. The survival rate of pediatric ALL patients has increased over last 50 years due to the application of highly standardized randomization treatment protocols. However, 10-20% of ALL patients will relapse and die in five year period after therapy completion. The survival rate of infants and adults with ALL is even worse. Increasing the cumulative doses of current protocols did not result in the improved survival rate, despite the higher incidence of toxic effects. Therefore, new therapeutic strategies are needed to improve the ALL therapy efficiency. The most promise hold the genetic and epigenetic drugs, as well as therapy with cells expressing chimeric antigen receptors (CAR), directed specifically towards cancer cells. Due to the unclear safety profile of the abovementioned therapeutics, these new approaches will be at first focused only on patients with resistant ALL.
Keywords: acute lymphoblastic leukemia; akutna limfoblastna levkemija; new therapeutic approaches; novi terapevtski pristopi; protokoli zdravljenja; randomized treatment protocols